2017
DOI: 10.1364/oe.25.014308
|View full text |Cite
|
Sign up to set email alerts
|

Long period fiber grating based on periodically screw-type distortions for torsion sensing

Abstract: A novel long-period fiber grating (LPFG), fabricated by periodically cascading a series of screw-type distortions, is proposed and experimentally demonstrated. These screw-type distortions are induced by twisting the fiber during CO laser beam exposure. The resulting LPFG will either be left- or right-hand helical, depending on the twist rate and direction used during fabrication, with a certain frozen shear strain. Due to the independence between grating pitch and twist rate, this type of LPFG could be more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 22 publications
0
31
1
2
Order By: Relevance
“…The measurement results showed that the torsion sensitivities of these samples were determined by the initial twist rate of PCFs and the RI of the infiltrated liquid materials. As such, an optimal torsion sensitivity of 446 nm·mm·rad −1 is obtained, which is higher than that of previous reports [18][19][20].…”
Section: Introductioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The measurement results showed that the torsion sensitivities of these samples were determined by the initial twist rate of PCFs and the RI of the infiltrated liquid materials. As such, an optimal torsion sensitivity of 446 nm·mm·rad −1 is obtained, which is higher than that of previous reports [18][19][20].…”
Section: Introductioncontrasting
confidence: 57%
“…On the other hand, once a non-standard RI liquid is filled in the twisted PCF, the torsion sensitivity will be enhanced if the effective RI corresponding to the resonant wavelength is larger compared to the case of using a standard RI liquid, and vice versa. [18] As shown in Table 2, the optimum torsion sensitivity of LFTPCFs is 446 nm•mm•rad −1 . A variety of previously reported fiber optic torsion sensors that employed different special fibers and structures are presented in Table 3 for comparison, where the achieved torsion sensitivity of the proposed sensor is far higher than that of the torsion sensor reported so far.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Different from the torsion sensors based on helical structures, a segmented‐LPFG has been reported for torsion measurement with enhanced sensitivity; however, with a relatively narrow dynamic range, which may be impractical for certain applications. Alternatively, an LPFG based on periodically screw‐type distortions was also reported for torsion sensing with enhanced linear sensitivity …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, an LPFG based on periodically screwtype distortions was also reported for torsion sensing with enhanced linear sensitivity. 11 In this Letter, we report a new fabrication technique of LPFGs using a commercial fusion splicer. The proposed method is based on axial rotation of the optical fiber at each arc discharge so that the induced asymmetric perturbation rotates by an axial angle of 180 along the axial direction of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The novel device was placed in a torsion test system 19) to observe the shift of the resonant dip with the increase of the torsion angle. One rotator was fixed, while the other one was rotated in the clockwise (+) or counterclockwise (−) directions, which were equal to or opposite to the direction of the twisting PCF, respectively.…”
mentioning
confidence: 99%